The Work Motivation Effect, Training, and Competence on the Employee Performance Over Kemayoran Hospital - Karyono Karyono; Rhian Indradewa; Tantri Yanuar R Syah (Penerbit Kemala Indonesia, 2020)
Employee performance is a result of quality and quantity of work by an official in carrying out duties at accordance with the responsibilities. Here, the motivation is a willingness to do their best to achieve organizational goals that also meet one's needs. While the training is an effort aimed to improve the quality of human resources. Thus, the competence is a set of knowledge, skills, and attitudes that must be possessed, internalized, mastered, and realized by someone in carrying out professional tasks without leaving aspects of personality and social abilities in carrying out their duties. The purpose of this research to determine Competency, Training, Work Motivation and Employee Performance aspects. Therefore, around 100 employees participated as respondents in this research. By using Structure Equation Modeling (SEM) and Linear Structural Relationship (LISREL) statistical software version 8.70, we analyze the result. Here, the results showed work motivation has an effect on competence and training has an effect on competence while work motivation did not have a significant effect on employee performance, training had an effect on employee performance and competence had an effect on employee performance.